THE EFFECT OF GAME THROUGH SMALL GROUPS IN TEACHING READING COMPREHENSION - Rusmiati (Getsempena English Education Journal, 2015)
This article describes about the effect of game through small groups in teaching reading comprehension. Generally, teachers used to be active then their students, Yet, in some ways it has been changed, students now tend to avoid the passivity in the class. Teachers role in this phase is the fasilitator from whom students run for guidance during their lesson. Students are also encouraged to be well spirited in using their skills in English conversationally by giving and sharing ideas. Therefore, learning through games is one of the most interesting technique to reach this great atmosphere of the class.